Sequential salvage systemic therapy after immunotherapy in head and neck cancer: a real-world study - Cabezas-Camarero, Santiago; Merino-Menéndez, Salomé; Cabrera-Martín, María Nieves; Pérez-Alonso, Pablo; Sotelo, Miguel J.; Pérez-Segura, Pedro (Frontiers in Oncology, 2026)
BackgroundIn recurrent/metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN) there is no established standard therapy after progression to immune checkpoint inhibitors (ICI). Retrospective and limited prospective studies have suggested that salvage chemotherapy after ICI (SCAI) may outperform historical pre-ICI data. We evaluated cetuximab-based SCAI outcomes in a real-world setting.MethodsObjective response rate (ORR), median duration of response (DoR), and median best percentage change in target lesions (PCTL) by Response Evaluation Criteria In Solid Tumors version 1.1 (RECIST 1.1), and median progression-free survival (PFS) and overall survival (OS) with SCAI and with last chemotherapy before immunotherapy (LCBI) were assessed. Adverse events (AEs) by Common Terminology Criteria for Adverse Events (CTCAE) 5.0 were evaluated during SCAI, as well as treatment exposure to cetuximab-based therapy and to ICI across the whole R/M setting.ResultsAmong 80 patients, 96% and 100% received cetuximab-based first and second SCAI, respectively, primarily as weekly (90%–94%) regimens, as follows. First SCAI: ORR of 59% (41/70; 31 partial and 10 complete responses), PCTL of −57% (range, −30% to −100%), DoR of 9.4 months, and PFS and OS of 5.9 and 12.4 months, respectively; first-line OS of 24 months. Cetuximab-based exposure (256 days) significantly exceeded ICI exposure (168.5 days; p = 0.038). LCBI-treated (n = 22): ORR of 36% (LCBI) vs. 47% (SCAI), PFS 8 months (LCBI) vs. 4.4 months (SCAI); first-line OS of 25.9 months. Second SCAI (n = 17): ORR of 30% (3/10), PFS and OS of 3.5 and 7 months, respectively; first-line OS of 21.7 months. Grade 1–2 AEs, 100%; grade 3–5 AEs, 38.7% (first SCAI) and 47% (second SCAI) with no toxic deaths.ConclusionCetuximab-based SCAI post-ICI showed high rates of response, which were durable and profound, and improved survival compared to historical data, with modest efficacy in re-sequenced patients. Time on cetuximab was significantly longer than on ICI. These results should be confirmed in a larger prospective study.